The 'patient voice': patients who experience antidepressant withdrawal symptoms are often dismissed, or misdiagnosed with relapse, or a new medical condition - Anne Guy; Marion Brown; Stevie Lewis; Mark Horowitz (SAGE Publishing, 2020)
Background: Stopping antidepressants commonly causes withdrawal symptoms, which can be severe and long-lasting. National Institute for Health and Care Excellence (NICE) guidance has been recently updated to reflect this; however, for many years withdrawal (discontinuation) symptoms were characterised as 'usually mild and self-limiting over a week'. Consequently, withdrawal symptoms might have been misdiagnosed as relapse of an underlying condition, or new onset of another medical illness, but this has never been studied. Method: This paper outlines the themes emerging from 158 respondents to an open invitation to describe the experience of prescribed psychotropic medication withdrawal for petitions sent to British parliaments. The accounts include polypharmacy (mostly antidepressants and benzodiazepines) but we focus on antidepressants because of the relative lack of awareness about their withdrawal effects compared with benzodiazepines. Mixed method analysis was used, including a 'lean thinking' approach to evaluate common failure points. Results: The themes identified include: a lack of information given to patients about the risk of antidepressant withdrawal; doctors failing to recognise the symptoms of withdrawal; doctors being poorly informed about the best method of tapering prescribed medications; patients being diagnosed with relapse of the underlying condition or medical illnesses other than withdrawal; patients seeking advice outside of mainstream healthcare, including from online forums; and significant effects on functioning for those experiencing withdrawal. Discussion: Several points for improvement emerge: the need for updating of guidelines to help prescribers recognise antidepressant withdrawal symptoms and to improve informed consent processes; greater availability of non-pharmacological options for managing distress; greater availability of best practice for tapering medications such as antidepressants; and the vital importance of patient feedback. Although the patients captured in this analysis might represent medication withdrawal experiences that are more severe than average, they highlight the current inadequacy of health care systems to recognise and manage prescribed drug withdrawal, and patient feedback in general.